Medicated chewing gum: An unconventional drug delivery system - Khatun, Sabera; Sutradhar, Kumar Bishwajit (International Current Pharmaceutical Journal, 2012)
Medicated chewing gum has a history for about a century. Now-a-days it is considered to be a potential and conve-nient modified release drug delivery system which can be used in pain relief medication, smoking cessation, travel illness, freshening of breath, prevention of dental caries, alleviation of xerostomia, vitamin or mineral supplementa-tion etc. Medicated chewing gums are prepared by using a water insoluble gum base with water soluble bulk portion. This formulation offers both local and systemic effects and has a range of advantages over conventional oral solid dosage forms. USP currently has no in vitro release testing apparatus for the evaluation and determination of drug release from the prepared chewing gums. But European Pharmacopoeia adopted a compendial apparatus to do so. Medicated chewing has drawn attention to the researchers as potential drug delivery system and it could be a com-mercial success in near future. Key Words: pharmaceutical chewing gum, gum base, oral mucosal drug delivery, buccal membrane, apparatus. DOI: http://dx.doi.org/10.3329/icpj.v1i4.10064 International Current Pharmaceutical Journal 2012, 1(4): 86-91